1
$\begingroup$

I am using the Stokes's theorem to evaluate the following line integral, $$ \oint_c y dx + x dy + (x^2 + y^2 + z^2) dz $$ where $C$ is the curve $x^2 + y^2 = 1, z = xy$ directed clockwise as viewed from the point $(0,0,1)$. I have

$$\oint_c y dx + x dy + (x^2 + y^2 + z^2) dz = \int \int_{S} \operatorname{curl}(y, x, x^2 + y^2 + z^2) \cdot \bar{n} dS$$


I am not looking to solve the full question right now, but I'm just wondering how to get $\bar{n}$ and $\operatorname{curl}$.
For $\bar{n}$ the solution is $$ \bar{n} = \frac{(y, x, -1)}{\sqrt{x^2 + y^2 + 1}}. $$ How do we get this result?
For the $\operatorname{curl}$ we have

$$ \begin{split} \operatorname{curl}(y, x, x^2 + y^2 + z^2) &= \begin{bmatrix} i & j & k \\ \frac{d}{dx} & \frac{d}{dy} & \frac{d}{dz} \\ y & x & x^2 + y^2 + z^2 \end{bmatrix}\\ \\ &= \begin{bmatrix} i & j & k \\ 0 & 0 & 2z \\ y & x & x^2 + y^2 + z^2 \end{bmatrix} \\ \\ & = i(-2zx) + j(2zy) + 0k \equiv (-2zx, 2zy, 0) \end{split} $$ while the stated answer of the exercise is $(2y, -2x, 0).$ What did I do wrong?

$\endgroup$
0
$\begingroup$

For any surface, eg $F(x,y,z)=f(x,y)-z=0$, the vector $\nabla F= \left(\dfrac{\partial F}{\partial x},\dfrac{\partial F}{\partial y},\dfrac{\partial F}{\partial z}\right)=\left(\dfrac{\partial f}{\partial x},\dfrac{\partial f}{\partial y},-1\right)$ is perpendicular to this surface, so, a vector normal and unitary is

$\bar n=\nabla F/|\nabla F|=\bar{n} = \dfrac{(y, x, -1)}{\sqrt{x^2 + y^2 + 1}}$

With $F(x,y,z)=xy-z$

I am not sure how you understood the determinant to calculate the curl but this is how the shorthand works (it's a purely formal device to facilitate calculations: we aren't in fact writing vectors into the determinant).

$ \operatorname{curl}(y, x, x^2 + y^2 + z^2) = \begin{vmatrix} i & j & k \\ \dfrac{\partial}{\partial x} & \dfrac{\partial}{\partial y} & \dfrac{\partial}{\partial z} \\ y & x & x^2 + y^2 + z^2 \end{vmatrix}=$

$=\left(\dfrac{\partial (x^2+y^2+z^2)}{\partial y}-\dfrac{\partial x}{\partial z}\right)i+\left(\dfrac{\partial y}{\partial z}-\dfrac{\partial (x^2+y^2+z^2)}{\partial x}\right)j+\left(\dfrac{\partial x}{\partial x}-\dfrac{\partial y}{\partial y}\right)j=2yi-2xj$

As expected.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.